Music for a Wedding - Clark, Lauren (Poet) (Pitt poetry series., 2017)
Lauren Clark's poems move lucidly, depicting beautiful struggles of distrust, dream, grief, and intimacy. They show such conflicts through entrancing narrative drive and song-like abandon. In their unpredictable, unforgettable language, they make pain a tonic for pleasure, sorrow ground for revelation. This is a book that is celebratory, gentle, and queer.